2005
DOI: 10.1103/physrevb.72.014416
|View full text |Cite
|
Sign up to set email alerts
|

Memory effects in a nanoparticle system: Low-field magnetization and ac susceptibility measurements

Abstract: A dilute magnetic liquid with Co nanoparticles with an average diameter of 5 nm in hexane has been studied systematically following the experimental approach proposed recently for observing memory effects in magnetic nanoparticles. All phenomena reported previously have been observed, which were earlier ascribed to the memory effect. However, the standard experiments for observing memory effects ͑low frequency as susceptibility and low field dc magnetization measurements͒ do not show the memory effect. To unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 22 publications
(39 reference statements)
6
45
0
2
Order By: Relevance
“…In a typical dc memory experiment, one should follow a stop-and-wait protocol consisting of three steps: 14,24 ͑a͒ cool the sample in a zero-field at a constant rate from a temperature, T H , which is much higher than T p , the peak temperature of ZFC curves; ͑b͒ stop the cooling process at a temperature, T w , below T p and wait for t w ͑=6 h, in our experiments͒ and then resume the cooling process down to T base ͑=5 K in our experiments͒; ͑c͒ apply a small field at T base and measure the magnetization with increasing temperature up to T H . The difference between the stop-and-wait ZFC curve and a reference ZFC curve ͑without stopping at T w ͒ at the temperature T w can be attributed to the memory effect.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a typical dc memory experiment, one should follow a stop-and-wait protocol consisting of three steps: 14,24 ͑a͒ cool the sample in a zero-field at a constant rate from a temperature, T H , which is much higher than T p , the peak temperature of ZFC curves; ͑b͒ stop the cooling process at a temperature, T w , below T p and wait for t w ͑=6 h, in our experiments͒ and then resume the cooling process down to T base ͑=5 K in our experiments͒; ͑c͒ apply a small field at T base and measure the magnetization with increasing temperature up to T H . The difference between the stop-and-wait ZFC curve and a reference ZFC curve ͑without stopping at T w ͒ at the temperature T w can be attributed to the memory effect.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that ⌬M depends strongly on the waiting time because of the logarithmic relaxation. 14,41 In addition, it also varies with T w . To reduce the complexity caused by the waiting time and T w , we fix the waiting time to be 2.16ϫ 10 4 seconds ͑i.e., 6 h͒ and the ratio of T w / T p ͑or T w / T F ͒ to be about 0.7, where the magnetic relaxation is neither too slow nor too fast to observe the memory effect.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…28,33 Absence of aging and memory effects in ZFC protocol confirms that the behavior of Co 3 O 4 nanoparticles is not spin glass like. 6,8,17,18 Thus below T P , observation of a bifurcation in FC and ZFC magnetization and a slow magnetic relaxation seems to correspond to a blocked state as observed in superparamagnetic particles. Presence of memory effects in FC protocol also support this inference.…”
Section: Behavior Below Tpmentioning
confidence: 77%